Systemically Important Banks in Indonesia: Findings From Multivariate GARCH Conditional Value at Risk - Arief, Usman; Husodo, Zäafri Ananto (UI Scholars Hub, 2019)
We investigate the systemically important banks in the Indonesian financial system usingMultivariate GARCH Conditional Value at Risk (CoVaR). The systemic risk measurement, ΔCoVaR,defined as the change from CoVaR in its benchmark state as a one-standard-deviation event to itsCoVaR under financial distress. We estimate the systemic risk contribution using 21 commercialbanks from January 2007 to December 2018. Our study reveals that the top five ranking systemicbanks are dominated by state-owned banks, and its ranking is consistently the same in the periodbefore, during, and after the global financial crisis. Finally, we empirically find that systemic riskin Indonesia is strongly affected by external factors rather than bank characteristics. Based on this finding, we suggest that the government should maintain the regulation of external effect rather than the domestic effect.